Comparison of the Effectiveness of Acceptance and Commitment Therapy (ACT) and Emotion-Focused Therapy (EFT) on Cognitive Distortions and Emotion Regulation in Women with Social Anxiety Disorder - Shafie Nezhad , Seyede Shahrbano; Bigdeli, Hossein; Sobhi Gharamaleki, Nasser (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted with the aim of determining the effectiveness of a task-based cognitive rehabilitation program on improving executive functions in children diagnosed with high-functioning autism spectrum disorder. This research employed a quasi-experimental design with a pretest–posttest structure and a control group. From the population of children with high-functioning autism spectrum disorder who attended rehabilitation centers and clinics in Tehran in 2024, a total of 30 children were selected using convenience sampling and were randomly assigned to experimental and control groups. The experimental group received 12 sessions of a 45-minute task-based cognitive rehabilitation intervention, whereas the control group did not receive any intervention. The Go/No-Go Test (Menon, Adleman, & White, 2001), the Color–Word Test (Stroop, 1935), and the N-Back Test (Kirchner, 1985) were employed as research instruments. Data were analyzed using repeated-measures analysis of variance. The findings indicated that the task-based cognitive rehabilitation program had a significant effect on improving components of executive functions (including attention, inhibition, and visuospatial working memory) in children with high-functioning autism (P ≤ .05). Based on the results, it can be concluded that the task-based cognitive rehabilitation program can be used as an effective intervention for enhancing executive functions in children with high-functioning autism spectrum disorder.